Climate Smart Livestock Feed and Forage Innovations Training Workshop - Mekonnen, Kindu; Seifu, Haimanot; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
16-18 May 2022, Bahir Dar – The AICCRA project in Ethiopia in collaboration with Africa RISING organized a training workshop on climate-smart livestock feed and forage innovations for the representatives of Amhara, Oromia, and SNNPR regional government offices livestock experts, universities and research centers participants with a total number of 25 participants have attained the training workshops. Opening and welcoming speech was made by Dr Likawent Yeheyis Director, Amhara Regional Agricultural Research Institute (ARARI). In his opening remarks, Dr Likawent presented the general overview of the Ethiopian feed and forage production and highlighted areas where all stakeholders need to work. Dr. Kindu Mekonnen, African RISING Ethiopian Highlands program leader also welcomed the participants and made a short briefing on what AICCRA project in partnership with Africa RISING trying to achieve in the Ethiopian Highlands. In his remark, Dr. Kindu mentioned that the design of this training to be more of experience sharing and learning for all of us. He requested participants to share the knowledge learned on feed and forage development in the training workshop with extension experts, development agents and farmers in the forms of ToT to their respective sites. He also urges participants to be active during the training and provide feedback and take valuable lessons.